MANFAAT ORIGAMI UNTUK MEDIA PEMBELAJARAN ANAK USIA DINI - Salma Rozana (Jurnal At-Tabayyun, 2019)
Learning is a complex process that happens to everyone throughout his life. The learning process occurs because of interactions between someone and other creatures in a good and enjoyable way, so the learning process feels more beneficial, but in reality it is often the teacher is confused when the process occurs Learning., learning process is often held formally and conventionally in schools all to direct changes in students in a planned manner, whether in knowledge, skill, or attitude. The learning process is heavily influenced by its learning environment which among other things is the media used. Nowadays media used to be impressed ordinary-ordinary so that the child bored and saturated. Media learning is very important in the process of learning especially at the children level, nowadays often happens teachers are good at teaching but not good at making media and otherwise teachers are good at making media but not good at teaching, teaching and Media of two things that are integral to the teaching and learning process. Origami one of the usual learning media used by Paud children, in addition to the material is safe, origami is also colorful – so children love to use it. Origami is also very easy to use as a medium according to the theme of activities.